Shanghai Pudong : urban development in an era of global-local interaction - Chen, Yawei (Sustainable urban areas, 2007)
This publication concerns large-scale urban area development in general, and in particular with gaining an understanding of the role played by global-local interaction in shaping the area development strategies in one particularly explosive urban project, the development of Shanghai's Pudong New Area. The Pudong development provides an extreme example of a situation in which interaction between global and local forces took place in a location whose boundaries had been closed to the outside world for almost forty years and in a period when doors and windows were beginning to open. The research led to a concrete interpretation of the tensions developing at district level and provided an example capable of representing the complexity and dynamics of current area developments. The practical question addressed by the research was: What were the main factors responsible for the speed achieved by the Pudong development? The associated theoretical question was To what extent did the development of the Pudong New Area reflect the characteristics of a developmental state?.